Resiliency tactics during financial crisis: The nonprofit resiliency framework - Searing, Elizabeth A. M.; Wiley, Kimberly K.; Young, Sarah L. (Nonprofit management & leadership, 2021)
The ability of nonprofits to weather hard times is a popular theme in the literature, yet most of the research is spent on predicting organizational closure. Unfortunately, this offers little guidance to nonprofits attempting to both survive and deliver services during crises. We use the lived experiences of 31 nonprofits—a mix of umbrella groups and direct human service providers—during the Illinois state budget impasse to understand nonprofit organization resilience in times of crisis. We establish the Nonprofit Resiliency Framework using qualitative analysis, mapping tactics in five areas: financial, human resources, outreach, program and services, and management and leadership. This study not only provides further empirical investigation of organizational resilience, but also useful advice for nonprofits on how to weather a complex financial crisis.